The outcomes and treatment strategies in metastatic soft tissue sarcoma treated with immunotherapy-based therapy: a three-center study - Liu, Zhiyong; Weitao, Yao; Cui, Kang; Gao, Songtao; Wang, Xin; Zhang, Peng; Wang, Jiaqiang (Frontiers in Immunology, 2025)
BackgroundPreclinical studies showed that cytotoxic agents and antiangiogenic agents had regulatory effects in the tumor immune microenvironment of soft tissue sarcoma (STS), and then enhance the antitumor effect of immunotherapy. This study was to investigate the efficacy and safety of immunotherapy-based therapy in metastatic STS.MethodsWe conducted a retrospective analysis in three centers where some patients received immunotherapy-based therapy consisting of immunotherapy alone or in combination with systemic agents (cytotoxic agents and/or antiangiogenic agents). The primary endpoints were median progression-free survival (mPFS) and median overall survival (mOS), and Kaplan-Meier method was used to compare survival.ResultsA total of 79 patients were included in this study. With the median follow-up of 14.2 months, the mPFS and mOS was 7.5 months and 19.5 months, respectively. The PFS (P < 0.01) and OS (P < 0.01) were significantly better in the alveolar soft part sarcoma (ASPS) group compared to the non-ASPS group. Patients who treated in ≤2 lines had longer PFS (P < 0.01) and OS (P < 0.01) compared to those in subsequent lines. Further analysis was performed according to histopathological types, in patients with ASPS, the combination of immunotherapy-based therapy resulted in a longer PFS (P < 0.01) compared to immunotherapy in monotherapy. Similarly, the patients treated in ≤2 lines had longer PFS (P=0.03) and OS (P < 0.01) compared to in subsequent lines. In patients with non-ASPS, patients with potentially sensitive sarcomas (undifferentiated pleomorphic sarcoma, dedifferentiated liposarcoma, myxofibrosarcoma, and angiosarcoma) had a longer PFS (P = 0.02) and OS (P = 0.03) compared to other subtypes. The OS (P = 0.03) for patients with potentially sensitive sarcomas treated in ≤2 lines showed a long trend compared to subsequent lines. Most adverse events reported were mild and tolerable.ConclusionsThe immunotherapy-based therapy showed promising activity in survival, especially in certain histological subtypes (undifferentiated pleomorphic sarcoma, dedifferentiated liposarcoma, myxofibrosarcoma, and angiosarcoma), as well as in combination treatment and in early lines. Prospective researches are needed to confirm the potential benefits.